Achievements of Tourist Development Corporation in domestic tourism - Ahmad Khairuddin, Nor Raihan; Hashim, Zainal Abidin; Othman, Norlela; Kamarudin, Mohd Asri; Maarof, Noormala; Muhammad, Amin Hussani (1986)
Tourism goes far back to the earliest history of human civilisation. During that period, people went from one place to another for religious or pilgrimage purposes . To this religious aspect of tourism has been added the new dimension of pleasure-tourism . However the importance of pleasure-tourism began to be officially recognised only about 40 years ago . Tourism has grown eight-fold in the past two decades. This industry expanded so fast that its' importance is now universally recognised. This can be exemplified by the fact that nearly every country in the world has a National Tourist Organisation to look after matters pertaining to tourism.